East Side Greenway: sustainable vision for vacancy in Kansas City’s East Side - Wagner, Caleb (Kansas State University, 2019)
Kansas City’s East Side was once a well defined area with connected communities and entertainment throughout. Over the years the East Side has deteriorated due to historical events that have displaced residents, reduced investment interest, and left a place overwhelmed with vacancy and forgotten culture. Recently there has been interest from the City of Kansas City, community development associations, and large investors to revitalize Kansas City’s East Side as an urban entity. These efforts are evident with Kansas City’s Revive the East Side initiative that looks at revitalizing areas of Kansas City that are severely distressed (Appendix G). This can also be seen in the KC Green Plan which focuses on implementing sustainable design into the future growth and revitalization of Kansas City as a whole. This report looks at utilizing vacancy as a platform to improve the ecological quality and community health in an urban environment. Through historical research, an in depth inventory and analysis study, and community engagement meetings, a projective design proposal was developed. This projective design focuses on the Prospect Corridor and how its vacancies can be assembled and designed for green infrastructure, park connections, and a way to reveal the buried history and culture of Prospect Avenue.
Keywords: Sustainable greenway vision